Wacana Tirta Selukat di Desa Adat Bayad - Dwitayasa, I Made (Sphatika: Jurnal Teologi, 2024)
Water is one of the means of offering. In Bali, until now, the worship of water is still very strong among the people. This is proven by the fact that there are still many holy places such as Tirta Empul, Mengening, and many other temples in Bali that have springs that are sacred to Hindus. However, not just any water can be used as an offering. To differentiate between ordinary water and holy water, several conditions are required, such as: place and purity. Ordinary water is water that is obtained from clean water places but is specifically used for prayer, such as the jun taneg water (ground water in temples/holy places) or specifically made in the temple area (utama mandala). This water is called toya anyar. Meanwhile, holy water, called ndenagn tirta, is water that has gone through a purification process either based on upacara/upakara or through a mantra process, meaning that the water has been asked before Ida Sanghyang Widhi Wasa so that it becomes tirta (holy water). One of the holy waters in Pakarman Bayad Village named Tirta Selukat. This holy water is located on a cliff surrounded by rice fields which is very sacred to the residents of Pakrman Bayad Village, as a means of purification during the Panca Yadnya ceremony